A sodium/potassium switch for G4-prone G/C-rich sequences - Luo, Yu; Živković, Martina Lenarčič; Wang, Jiawei; Ryneš, Jan; Foldynová-Trantírková, Silvie; Trantírek, Lukáš; Verga, Daniela; Mergny, Jean-Louis (Nucleic acids research, 2024)
Metal ions are essential components for the survival of living organisms. For most species, intracellular and extracellular ionic conditions differ significantly. As G-quadruplexes (G4s) are ion-dependent structures, changes in the [Na+]/[K+] ratio may affect the folding of genomic G4s. More than 11000 putative G4 sequences in the human genome (hg19) contain at least two runs of three continuous cytosines, and these mixed G/C-rich sequences may form a quadruplex or a competing hairpin structure based on G-C base pairing. In this study, we examine how the [Na+]/[K+] ratio influences the structures of G/C-rich sequences. The natural G4 structure with a 9-nt long central loop, CEBwt, was chosen as a model sequence, and the loop bases were gradually replaced by cytosines. The series of CEB mutations revealed that the presence of cytosines in G4 loops does not prevent G4 folding or decrease G4 stability but increases the probability of forming a competing structure, either a hairpin or an intermolecular duplex. Slow conversion to the quadruplex in vitro (in a potassium-rich buffer) and cells was demonstrated by NMR. 'Shape-shifting' sequences may respond to [Na+]/[K+] changes with delayed kinetics.
Keywords: Potassium; Sodium; G-kvadruplexy; magnetická rezonanční spektroskopie; mutace; Magnetic Resonance Spectroscopy; lidé; sodík; Mutation; draslík; Humans; G-Quadruplexes